Development, Climate Change and Human Rights from the Margins to the Mainstream? - Cameron, Edward (World Bank, Washington, DC, 2017)
Since 2005, a growing number of vulnerable communities and nations have used the human rights lexicon to argue their case for an urgent and ambitious response to climate change. The purpose of this Social Development Department Working paper is to examine the emergence of a new discourse linking climate change and human rights, and to assess its social and political implications, particularly as they relate to development practitioners. The scope of this paper is to explore what relevance this new discourse has on what David Kennedy calls the 'vocabularies, expertise, and sensibilities' of development practitioners (Kennedy 2005). The methodology for this paper involved interviews with academics and policy practitioners who have shaped this emerging discourse; a wide-ranging literature review of texts relevant to the fields of development, climate change and human rights; discussions with development professionals who have the daily responsibility of operationalizing approaches to reducing vulnerability and building resilience; and finally drawing upon the author's own experience leading the Maldives' government's initiative on the Human Dimensions of Climate Change and as a consultant within the Social Dimensions of Climate Change Cluster of the World Bank's Social Development Department. It is important to stress that this paper is not a legal piece. Human rights are as much about ethical demands, calls for social justice, public awareness, advocacy, and political action as they are concerned with legal norms and rules. Sen has pointed out a 'theory of human rights cannot be sensibly confined within the juridical model in which it is frequently incarcerated' (Sen 2004, 319). Consequently this piece will focus on the wider, political economy aspects of the interface between human rights and climate change. It is further appropriate to state that this is not an advocacy piece. The paper deliberately avoids being normative or prescriptive in recommending a human rights-based approach to developing climate change operations. It does examine why vulnerable populations chose to embrace this approach, why they continue to view it as a transformative strategy, and what some of the successes and challenges have been.